2015
DOI: 10.1007/s10654-015-0080-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between early body mass index trajectories and later metabolic risk factors in European children: the IDEFICS study

Abstract: Faster growth seems to be a common factor in several hypotheses relating early life exposures to subsequent health. This study aims to investigate the association between body mass index (BMI) trajectories during infancy/childhood and later metabolic risk in order to identify sensitive periods of growth affecting health. In a first step, BMI trajectories of 3301 European children that participated in the multi-centre Identification and Prevention of Dietary and Lifestyle-induced Health Effects in Children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 52 publications
3
26
2
Order By: Relevance
“…As a result, each component had the same weight in the total score, and higher scores indicate a less favourable metabolic profile. This MetS demonstrates a clear association with anthropometry (Bornhorst et al, ).…”
Section: Methodsmentioning
confidence: 98%
“…As a result, each component had the same weight in the total score, and higher scores indicate a less favourable metabolic profile. This MetS demonstrates a clear association with anthropometry (Bornhorst et al, ).…”
Section: Methodsmentioning
confidence: 98%
“…In a study of 1124 children from England and Wales, both a lower birthweight and a higher childhood ponderal index were associated with higher fasting and postload insulin levels at 10-11 years, with stronger effect estimates for the childhood ponderal index [25]. Furthermore, a recent study among 3301 European children with a mean age of 8.5 years showed that rapid BMI growth between 9 months and 6 years was related to a higher risk of insulin resistance [27]. In our current study, growth during fetal life was not associated with childhood insulin or C-peptide levels, independent of growth in other time intervals.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…impaired glucose tolerance and diabetes) in adults. 35,36 Waist circumference is a well-known estimate of abdominal fat in adults, but little has been studied in children in this regard. 18 In this sense, Brambilla et al 37 assessed the association between waist circumference and visceral and subcutaneous abdominal adipose tissue measured by magnetic resonance imaging in children from 7 to 16 years old.…”
Section: Table 1 Continuedmentioning
confidence: 99%